Emergency preparedness in fitness facilities: bridging the gap between policy and practice. (2018) - Sekendiz, Betul; Norton, Kevin; Keyzer, Patrick; Dietrich, Joachim; Coyle, Ian R.; Gray, Shannon; Finch, Caroline F.
Fitness facilities are an important contributor to economies through preventative health policies of governments. Therefore, it is crucial that they are capable of ensuring the health and safety of their users during emergency situations under relevant work health and safety (WHS) legislation. This study aimed to analyse emergency response preparedness in fitness facilities in Australia and develop evidence-based strategic recommendations, using a mixed methods approach. An onsite observational audit tool and in-depth interviews were conducted at a sample of regional and metropolitan fitness facilities. The results showed that fitness facilities showed a lack of operational emergency response practices that requires an integrated approach to risk management by fitness facility operators. This gap between policy and practice has significant implications for all stakeholders involved in fitness service provision, including government agencies, academia and industry governing organisations.